Effect of cadmium on germination, coleoptile and root growth of barley seeds in the presence of gibberellic acid and kinetin - Munzuroglu, Omer; Zengin, Fikriye Kirbag (Triveni Enterprises, 2006)
Effect of cadmium on barley seeds treated with kinetin and gibberellic acid was investigated As usual, cadmium has inhibited seed germination, and showed important inhibitory effects on roots and coleoptile growth after germination. In general, increase in cadmium concentration caused a greater inhibition of germination, root and coleoptile, growth. The adverse effect of cadmium on root and coleoptile, growth was more pronounced than that on germination. While testa was pierced by radicle (an indication of germination), no root or coleoptile development was observed above at concentration of 3-9.5 mM CdCl2 center dot H2O. Low concentrations of cadmium have inhibited the root growth more than it did on coleoptile growth. Treatment of seeds with gibberellic acid and kinetin did not show any significant difference on the effect of cadmium in germination. However, inhibition of coleoptile elongation by cadmium has decreased a very much after kinetin application. The same result, although with lower rates when compared to kinetin, has been obtained for GA(3) as well. In addition, the inhibitory effect of cadmium on root growth increased even more after kinetin application. The results have been found statistically significant through the least significant different (LSD) test at levels of p < 0.05 and p < 0.01.
Keywords: cadmium; germination; gibberellic acid; kinetin; root and coleoptile growth